2019
DOI: 10.18632/aging.102235
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the retrograde axonal transport by curcumin promotes autophagic flux in N2a/APP695swe cells

Abstract: The accumulation of autophagosomes and dysfunction at the axonal terminal of neurons play crucial roles in the genesis and development of Alzheimer’s disease (AD). Abnormalities in neuron axonal transport-related proteins prevent autophagosome maturation in AD. Curcumin, a polyphenol plant compound, has been shown to exert neuroprotective effects by increasing autophagy in AD, but the underlying mechanism of its effect on autophagy axon transport remains elusive. This study investigated the effects of curcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Therefore, balanced autophagosome production and degradation are a prerequisite for neuroprotection in AD. In our previous study, we observed that several autophagosomes could not successfully combine with lysosomes to form mature autophagic lysosomes in AD model N2a/ APP695swe cells transfected with a double-labeled autophagic adenovirus (mRFP-GFP-LC3) [26]. Dynein intermediate chain (DIC) is required for autophagosome transport and autophagic lysosome maturation, and it has been reported that DIC expression is downregulated in the brain of patients with AD [27].…”
Section: Agingmentioning
confidence: 99%
“…Therefore, balanced autophagosome production and degradation are a prerequisite for neuroprotection in AD. In our previous study, we observed that several autophagosomes could not successfully combine with lysosomes to form mature autophagic lysosomes in AD model N2a/ APP695swe cells transfected with a double-labeled autophagic adenovirus (mRFP-GFP-LC3) [26]. Dynein intermediate chain (DIC) is required for autophagosome transport and autophagic lysosome maturation, and it has been reported that DIC expression is downregulated in the brain of patients with AD [27].…”
Section: Agingmentioning
confidence: 99%
“…In addition to rapamycin, curcumin, a natural compound that inhibits the PI3K/Akt/mTOR pathway, has been described as having a therapeutic effect on neurodegenerative diseases [228,229]. Curcumin has been shown to enhance the expression levels of autophagy-related proteins, such as Beclin-1, ATG5, or ATG16L1, and motor proteins essential for retrograde axonal transport, resulting in an increase of the autophagic flux and the clearance of intracellular aggregates [113,228,230,231].…”
Section: Mtor-dependent Autophagy Inducing Agentsmentioning
confidence: 99%
“…A of AMPK activity (226)(227)(228)(229)(230). Moreover, curcumin may promotes autophagic proteins and their retrograde axonal transport (231).…”
Section: Neurodegenerative Diseases 821 Alzheimer's Diseasementioning
confidence: 99%